THE INFLUENCE OF CONCEPT MAP AND GAMES TECHNIQUE ON LEARNING ACHIEVEMENT AND LEARNING MOTIVATION - Ristianingsih, Iis; Wardoyo, Cipto; Achadiyah, Bety Nur (Universitas Negeri Malang, 2016)
This study examines whether concept map and games technique influence learning achievement differently. This study is a quantitative research using quasy experiment method. The population used in this study is all students in SMA Negeri 6 Malang (Public High School). Cluster random sampling is used to obtain 32 students of class XI IPS 5 to apply concept map and 32 students of class XI IPS 4 to apply games technique. Descriptive statistics, independent sample t-test, and Mann Whitney U are employed to analyze the data. The results of this study show that (1) there is significantly differences between the implementation of concept map and games technique toward learning achievement, and (2) there is no significantly differences between the implementation of concept map and games technique toward learning motivation.Keywords: concept map, games technique, learning achievement, learning motivation